The external politics of the United States and the Cuban development - Ayerbe, Luis Fernando (Universidade Estadual Paulista / UNESP, 2009)
The article analises the development of Cuban economy after the 1959 revolution, emphasizing the following aspects: a) the relevance of the United States foreign policy; b) how the Cuban economic and political model provoked the current crisis and affected the capability to face it; c) the post cold war context of Cuban-United States relationships.